(untitled) (Higher Education Politics and Economics, 2022)
State support for higher education has been volatile, prompting public universities to pursue alternative revenue sources to supplement state support. While dependence on alternative revenue sources has been raising, the relationship between these revenue sources and graduation rates has not been examined in depth. This study uses a panel data from 2012-2018 to examine how alternative revenue sources related to graduation rates by institution type and student race. The results showed that the associations among alternative revenue sources and graduation rates varied by institution type and racial group. The results also showed that relying on alternative revenue other than state funding may negatively influence graduation rates for all student racial groups. The discussion and implications for practice are presented.